KONSTRUKSI PEMIKIRAN ISLAM M. ARKOUN; KRITIK TERHADAP NALAR ISLAM DAN NALAR MODERN - Rahman, Arif Aulia (ISTINBATH JURNAL HUKUM, 2010)
AbstractArkoun finds even secularist and reformist Muslims who are still prisoners, in their discourse of the problematic thrown up by the Modernity of the Classical Age (1800-1950), imposed by the so-called revolutionary civilized Europe until at least 1950. In order to transcend this impasse, Muslims must undertake a radical double critique: western Modernity and the Islamic heritage, with the aim of transcending both, instead of just trying to come to terms with the European modernity while still prisoner to a heritage that is uncritically re appropriated. This article shows that Arkoun interpret the modernity that is based on philosophical, more than just a historical or sociological sense. Arkoun distinguish between "material" modernity and "intellectual" or "cultural" modernity. The first means that the various advances that occurred in the outer frame of the human form, while the latter includes the methods, analytical tools, and intellectual attitude that gives the ability to understand reality. There are some important notes about the criticism of Islamic rationality, particularly relating to religion and truth values of Islam, and the construction of Islamic reasoning and modern rationality. That the reasoning required in meaning a comprehensive understanding of aspects of the historical, socio-cultural, socio-political, and religious. Included also to look at the textual and contextual issues.Â Keywords: Arkoun, Reason, Logosentrism.